Research of the efficiency of the one-step process for producing carbon steels on the territory of modern Belarus in the pre-industrial period. Foundry production and metallurgy - D. V. Andreev (Литьë и металлургия)
The article describes experiments on the reconstruction of the technology of the one-step process of obtaining iron-carbon alloys in furnaces based on archaeological sources. It contains the description of furnace design, metallurgical process technology and raw materials preparation. The process of refining the iron bloom by forging is described. Scientifically grounded assumptions are made about possible technological methods of obtaining steels in the pre-industrial period on the territory of modern Belarus.